2015
DOI: 10.1111/jfbc.12187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chemical Composition, In Vitro Inhibition of Cholinergic and Monoaminergic Enzymes, and Antioxidant Potentials of Essential Oil from Peels and Seeds of Sweet Orange (Citrus Sinensis [L.] Osbeck) Fruits

Abstract: This study was designed to compare the chemical compositions and effect of essential oils from the peels and seeds of sweet orange on cholinergic (acetylcholinesterase [AChE], butyrylcholinesterase [BChE]) and monoaminergic (monoamine oxidase [MAO]) enzymes. The ability of the essential oils to protect the brain against Fe2+‐induced lipid peroxidation was also investigated. Forty and forty‐four compounds were identified in peels and seed essential oils, respectively, using gas chromatography. The essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Considering the ex tracts inhibitory effectiveness as revealed by the EC 50 values (Table 1), there was no significant difference (P N 0.05) in the inhibitory effects of the extracts (editan = 1.03 ± 0.08 μg/mL; utazi = 0.13 ± 0.03 μg/mL; afang = 0.16 ± 0.04 μg/mL). These findings also agree with earlier studies on the MAO inhibitory properties of plant phyto chemicals; Zhi et al [6], reported that phytoconstituents from leaf of Desmodium elegans are potent MAO inhibitor, while Ademosun et al [33], reported MAO inhibitory properties of essential oils from peel and seed of sweet orange as part of their neuroprotective properties. Therefore, the ability of the extracts in this study to inhibit MAO activity could be another mechanism contributing to their neuroprotective properties, and could be essential for the prevention and management of neurodegeneration.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Considering the ex tracts inhibitory effectiveness as revealed by the EC 50 values (Table 1), there was no significant difference (P N 0.05) in the inhibitory effects of the extracts (editan = 1.03 ± 0.08 μg/mL; utazi = 0.13 ± 0.03 μg/mL; afang = 0.16 ± 0.04 μg/mL). These findings also agree with earlier studies on the MAO inhibitory properties of plant phyto chemicals; Zhi et al [6], reported that phytoconstituents from leaf of Desmodium elegans are potent MAO inhibitor, while Ademosun et al [33], reported MAO inhibitory properties of essential oils from peel and seed of sweet orange as part of their neuroprotective properties. Therefore, the ability of the extracts in this study to inhibit MAO activity could be another mechanism contributing to their neuroprotective properties, and could be essential for the prevention and management of neurodegeneration.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, it is of interest that the extracts showed higher BChE inhibitory effect than AChE. Previous findings have also reported the ability of plant extracts to inhibit BChE activity better than AChE (in vitro) [33,34]. Impairment of the monoaminergic neurotransmission through rapid oxidation of monoamine neurotransmitters by MAO has been implicat ed in the pathogenesis and progression of several neurodegenerative diseases, especially PD and AD [35].…”
Section: Resultsmentioning
confidence: 95%
“…; Ademosun et al . ). Therefore, to achieve the holistic treatment/management of neurodegenerative disease and cognitive dysfunction, these enzymes should be co‐inhibited so as to restore ACh level and prevent indiscriminate hydrolysis of monoamine neurotransmitter with a positive increase in serotonergic and catecholaminergic compound in AD patient as reported by Ademosun et al .…”
Section: Introductionmentioning
confidence: 97%
“…Penile homogenate was prepared according to the method of Belle et al (2004) and lipid peroxidation assay was determined using the method of Ademosun et al (2016). The rat penile homogenate (100 lL) was mixed with a mixture containing 30 lL of 0.1 M Tris-HCl buffer (pH 7.4), extract and 30 lL of 250 lM Fe 2þ .…”
Section: Preparation Of Penile Homogenate and Lipid Peroxidation Assaymentioning
confidence: 99%